A novel approach for simultaneous differentiation of closely related meat species by PCR assay using single primer pair - MANE, B G; MENDIRATTA, S K; TIWARI, A K; NARAYAN, RAJ (The Indian Journal of Animal Sciences, 2012)
The aim of the present study was to design the primer pair for differentiation of closely related meat species i.e. cattle from buffalo, and sheep from goat employing PCR assay. The primer pair was designed based on the mitochondrial 12S rRNA gene sequences of buffalo and then designed primer pair matched with other species available 12S rRNA gene sequences. The designed primer pair was successfully amplified to the desired DNA fragments of 316 bp from the buffalo and sheep in single PCR reaction assay without any cross reaction with cattle, goat, pig and chicken species. The developed PCR assay was able to differentiate the closely related meat species; however, this assay was not suitable for differentiation of buffalo from sheep species meat. This PCR assay was also effective in heat treated meat and meat emulsion without any adverse effect on amplification of DNA. It can be concluded that the developed PCR assay has potential application for the purpose of differentiation of closely related meat species.